Somatic gene delivery faithfully recapitulates a molecular spectrum of high-risk sarcomas - Imle, Roland; Blösel, Daniel; Kommoss, Felix; Placke, Sara; Stutheit-Zhao, Eric; Blume, Christina; Lupar, Dmitry; Schmitt, Lukas; Winter, Claudia; Wagner, Lena; von Eicke, Malte; Walzer, Hannah; et al. (Nature Communications, 2025)
A major challenge hampering therapeutic advancements for high-risk sarcoma patients is the broad spectrum of molecularly distinct sarcoma types and the corresponding lack of suitable model systems. Here we describe the development of a genetically-controlled, yet versatile mouse modeling platform allowing delivery of different genetic lesions by muscle electroporation (EPO) in wildtype mice. This EPO-GEMM (EPO-based genetically engineered mouse model) platform allows the generation of ten genetically distinct sarcomas on an isogenic background, including the first model of ETV6::NTRK3-driven sarcoma. Comprehensive histological and molecular profiling reveals that this mouse sarcoma cohort recapitulates a spectrum of molecularly diverse sarcomas with gene fusions acting as major determinants of sarcoma biology. Integrative cross-species analyses show faithful recapitulation of human sarcoma subtypes, including expression of relevant immunotherapy targets. Comparison of syngeneic allografting methods enables reliable preservation and scalability of sarcoma-EPO-GEMMs for preclinical treatment trials, such as NTRK inhibitor therapy in an immunocompetent background.